Pengaruh Frekuensi Pemberian Pakan Terhadap Pertumbuhan Kepiting Bakau (Scylla serrata) Pada Recirculating Aquaculture System (RAS) - Mayzuri, Zavira; Lubis, Amelia Sriwahyuni; Kamal, Eni (Jurnal Perikanan Unram, 2025)
Recirculating Aquaculture System (RAS) was chosen as an alternative for sustainable and low-impact mangrove crab cultivation. One of the main challenges in using RAS is determining the optimal feeding frequency. Inappropriate feeding can cause slow growth, increased mortality, and decreased water quality. This study aimed to analyze the effect of trash fish feeding frequency on the growth of mangrove crab (Scylla serrata) reared in RAS. The method used is an experimental method with a completely randomized design of 3 treatments and 4 replications. The research treatments tested were the frequency of feeding with FPP 01 once a day at 10 pm; FPP 02 twice a day at 10 pm and 5 pm; FPP 03 three times a day at 10 pm, 8 am and 5 pm. The parameters observed were survival, weight growth, carapace length growth, carapace width growth, specific growth rate and molting rate. The research data were analyzed using analysis of variance at a 95% significance level. The results showed that the frequency of feeding did not significantly affect the growth and survival of mud crabs in RAS. The frequency of feeding once is optimal to achieve maximum growth in mud crab cultivation using the RAS system with a survival rate of 100±0.00%, weight growth of 52.00±21.17 g, carapace length growth of 1.90±0.87 cm, carapace width growth of 1.60±0.70 cm, specific growth rate of 5.04±0.14%/day and molting rate of 67.00±0.58%.